A COMPARATIVE STUDY OF CONDUCTIVE AND DIRECT METHOD OF AGNIKARMA WITH TAMRA SHALAKA IN SANDHIGATVATA WITH SPECIAL REFERENCE TO OSTEOARTHRITIS OF KNEE JOINT - lata, Anju; Badwe, *Yogesh; Vaidya, Umesh (International Journal of Ayurveda and Pharma Research, 2015)
In day to day practice we come across a situation where in patients are on long term NSAID, as well as steroids, but comparing with their side effects pain relief is not very good. So here we have to find out some better treatment for the same which can minimize their analgesic and steroid dependency. The five types of Vatadosha owing to causes get vitiated and manifest in places all over the body. In old age because of Dhatukshaya, vata prakopa occurs mainly in bones and joints this leads to Sandhigata vata (Osteoarthritis).Agnikarma can be performed in intense pain caused by vata situated in skin, muscle, blood vessel, ligament, joint and bone, wound with hard raised granulation, in cysts, piles, tumors, fistula-in-ano, Apachi, elephantiasis, warts, moles, inguinal hernia, disease of joints, cutting of blood vessel, sinus and in excessive haemorrhage.There are so many conservative treatments described in Ayurveda for Sandhigatvata as said by Acharya Susruta in Su.Chi. 4/8 but Agnikarma is best one among them as described in Su.Su.12/3. Many studies were conducted in Sandhigata vata, especially on Agnikarma. Here we have compared the efficacy of conductive and direct method of Agnikarma with Tamra shalaka in Sandhigatvata (osteoarthritis) of knee joint. Symptomatic Osteoarthritis of the knee occurs in 12% of persons age â‰¥60 and 6% of all adults age â‰¥30. The prevalence of Osteoarthritis rises strikingly with age. Regardless of how it is defined, Osteoarthritis is uncommon in adults under age 40 and highly prevalent in those over age 60. It is a common disease that is at least in middle-aged and elderly persons, is much more common in women than in mens.